Given the functions p(x) and q(x) defined as:
![\begin{gathered} p(x)=x^2+3 \\ q(x)=\sqrt[]{x+2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/en8yam63eszj7u1g3vwbj5nnod9395f4bs.png)
We can use the definition of composite functions:

Then, to calculate (p o q)(2) = p(q(2)), we need to calculate q(2) first:
![q(2)=\sqrt[]{2+2}=\sqrt[]{4}=2](https://img.qammunity.org/2023/formulas/mathematics/college/vn1lp7fx16iqw02ukayk67n7ixujp4epwx.png)
Using this result on the composition:

Now, for (q o p)(2) = q(p(2)), we already calculate p(2) = 7. Then:
![\begin{gathered} (q\circ p)(2)=q(p(2))=q(7)=\sqrt[]{7+2}=\sqrt[]{9} \\ \Rightarrow(q\circ p)(2)=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rwud8dk9p0ma2g1zrwrl4736sd1mndss53.png)